Association between behavioural, metabolic risk factors of non-communicable diseases and socio-demographic factors among Bihari population in Bangladesh - Ahmed, Sabrina; Mansur Ahmed, M. S. A.; Banik, Palash C.; Mondal, Rajib; Sen Gupta, Pradip K. (International Journal Of Community Medicine And Public Health, 2019)
Background: The Bihari community is an underprivileged group of people, immigrants from Pakistan during 1971 independence war, now living in Bangladesh. This community is considered as vulnerable for not having adequate health care facilities and access to health services. The current study is aimed to determine the association between behavioural, metabolic risk factors of non-communicable diseases (NCD) and socio-demographic factors among Bihari community in Bangladesh. Methods: It was a community based cross-sectional study. Total 183 Bihari living in Geneva camp in Dhaka city have been included in the study by purposive sampling. An adopted WHO STEPS questionnaire was used for data collection. A semi structured questionnaire and standardized procedures were used to measure behavioural risk factors and physical characteristics. Data were analysed by using SPSS version 21. Results: Among the respondents the mean age was 44.4±13.2 years with 60.1% men. One-third (32.2%) were current tobacco user, almost all (99.5%) didn’t take sufficient fruit and vegetables, 52.5% were added salt user, 76.0% didn’t perform adequate physical activity but alcohol consumers were negligible (3.3%). More than half (54.6%) were overweight or obese, 33.9% had hypertension, 23.0% had hyperglycaemia and 50.3% had hyperlipidaemia. Sex, age, education, occupation and family income were significantly associated with these NCD risk factors. Conclusions: To our best knowledge this is the first ever study that describes the NCD risk factors and its sociodemographic determinants among the Bihari population in Bangladesh.